PENGEMBANGAN LKS IPA BERBASIS WORD SQUARE MODEL KETERPADUAN CONNECTED - Ulfah, Anik; Bintari, Siti Harnina; Pamelasari, Stephani Diah (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2013)
Penelitian ini bertujuan untuk mengetahui kelayakan dan keefektifan LKSberbasis word square tema pencemaran lingkungan yang telah dikembangkanuntuk digunakan di SMP/ MTs. Subjek penelitian dibagi menjadi dua kelompokyaitu kelompok skala kecil dan kelompok skala besar. Metode pengumpulan datamenggunakan metode dokumentasi, observasi, tes, dan angket. Berdasarkan hasilvalidasi dari pakar dan guru pada tahap I dan tahap II dinyatakan layak. Pada ujicoba skala kecil menunjukkan bahwa tanggapan siswa sebesar 82%, dan nilaihasil belajar siswa sebesar 93% siswa diatas KKM. Pada uji coba skala besartanggapan siswa sebesar 99%, hasil rata-rata observasi aktivitas siswa sebesar83%, dan nilai hasil belajar siswa pada uji coba skala besar sebesar 95% diatasKKM. Berdasarkan hasil penelitian dapat diambil kesimpulan bahwa LKS hasilpengembangan berbasis word square tema pencemaran lingkungan layak danefektif digunakan sebagai bahan ajar dalam pembelajaran IPA di SMP/ MTs. This research is aimed to f the ind out feabisility and effectiveness of “LKS” based on wordsquare, with Environmental Pollution theme that has been developed to be used in juniorhigh school. The subject of this study was divided into two groups, they were small scalegroup and large scale group. The data were collected by using documentation, observation,test, and questionnaire methods. Based on the validation of experts consisting of lecturerand teacher validation in phase I and phase II, it is obtained that the result of“LKS”validation is feasible. The trial of a small scale group showed that the students’response reachedto be used as 82 % and value the students’ achievement was 93 % itreached minimum mastery criteria. The trial of large scale phase showed that the students’response reached 99 %, the average result observation the activity of students reached 83 %,and value the students’ achievement of the students in the trial of a large scale was 95 %above minimum mastery criteria. Based on the result it can be concluded that “LKS”based on word square the Environmental Pollution theme is feasible and effective to be usedas teaching materials in learning IPA in junior high school.